2020
DOI: 10.3390/nano10071417
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Modified Carbohydrates on the Size and Shape of Gold and Silver Nanostructures

Abstract: Gold (Au) and silver (Ag) nanostructures have widespread utilization from biomedicine to materials science. Therefore, their synthesis with control of their morphology and surface chemistry have been among the hot topics over the last decades. Here, we introduce a new approach relying on sugar derivatives that work as reducing, stabilizing, and capping agents in the synthesis of Au and Ag nanostructures. These sugar derivatives are utilized alone and as mixture, resulting in spherical, spheroid, trigonal, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, stability of CA mediated AuNSs were not high (completely clumped within 48 h and require extensive vortexing) so further morphological analysis were not performed. This could be related to that CA extract gave lesser amount of proteins and carbohydrates than PN and JO extract, where proteins and carbohydrates can serve as stabilizing agent [36,37].…”
Section: Figure 5bmentioning
confidence: 98%
“…However, stability of CA mediated AuNSs were not high (completely clumped within 48 h and require extensive vortexing) so further morphological analysis were not performed. This could be related to that CA extract gave lesser amount of proteins and carbohydrates than PN and JO extract, where proteins and carbohydrates can serve as stabilizing agent [36,37].…”
Section: Figure 5bmentioning
confidence: 98%
“…The emergent need to find biocompatible, non-toxic, and green chemicals for the synthesis of nanobiomaterials has driven researchers to test natural molecules as ligands for MNPs [ 81 , 82 ]. Among them, proteins [ 83 , 84 ], peptides [ 85 , 86 ], amino acids [ 87 ], carbohydrates [ 88 , 89 ], and plant extracts [ 90 , 91 ] have been demonstrated to have a big impact on the biochemical, photophysical, and physical–chemical properties of MNPs. Moreover, recently, AuNCs capped with biomolecules showing superior properties have been reported in the literature.…”
Section: Design and Application Of Auncs For Bioimagingmentioning
confidence: 99%
“…The fungi P. italicum was successfully identified over related fungi species Trichaptum biforme , Glomerulla cingulata ( Colletotrichum gloeosporioides ), and Aspergillus nidulans . The authors concluded that this specificity resulted from the sugar ligands employed in the synthesis of the gold nanoparticles and was unaffected by their size and shapes [ 216 ].…”
Section: Nanosensor Applications In Plantsmentioning
confidence: 99%